Recent progress on porous carbon and its derivatives from plants as advanced electrode materials for supercapacitors - Jiang, Guosai; Senthil, Raja Arumugam; Sun, Yanzhi; Kumar, Thangvelu Rajesh; Pan, Junqing (Journal of power sources, 2022)
Porous carbon (PC) materials have been extensively employed as electrodes in the energy storage field owing to their large specific surface area (SSA), high durability and unique inner structure. Ulteriorly, the development of new energy-storage systems definitely demands sustainable, low-priced and environmentally nonharmful electrode materials. Many researchers have shifted attention to plant materials and made many efforts, considering that the precursors are rich in carbon elements, easy to scale up, and possess unique channel structures. This review makes retrospect about the recent researches on plant-derived carbon for supercapacitor application, particularly focusing on the influence of structure and components of materials on electrochemical performance. Firstly, the synthesis methods, including physical and chemical activation are discussed in detail. Secondly, multi-component carbon materials, especially heteroatom doping and composite carbon for improving electrochemical performance are also revealed systematically, which contribute to design electrode materials with adjustable pore-size distribution and eligible structure for rapid transport of electrolyte ions and electrons, and hopefully can provide valuable guidance for making full use of the characteristics of plant materials for energy storage. Finally, we put forward current challenges and development trends based on plant-derived carbon materials for supercapacitor application. [Display omitted] •Porous carbon derived from plants has the advantages of resource and cost.•The choice of precursor and activation method is critical to boosting performances.•Heteroatom doping can effectively improve the surface properties of porous carbon.•Plant-based composite materials achieve enhanced energy density than pure carbon.